Peran Hypnobreastfeeding dalam Optimalisasi Praktik ASI Eksklusif pada Ibu Menyusui di Kelurahan Bojongkerta Kota Bogor Tahun 2025 - Triswanti Triswanti; Shafa Eka Zivana Tanjung; Irmawati Irmawati; Ira Yulia; Dinda Tri Rahmatillah; Anisah Rasikah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Exclusive breastfeeding for the first six months of a baby's life is an important strategy to support optimal growth and development. Breast milk has many benefits for babies, such as strengthening the immune system and supporting brain development. However, various obstacles such as emotional stress, lack of self-confidence, and minimal support from family and the community remain significant barriers to successful breastfeeding. These issues often lead to failure to provide exclusive breastfeeding in accordance with health recommendations. This study aimed to evaluate the effectiveness of hypnobreastfeeding training in improving breastfeeding knowledge, attitudes, and practices among mothers with infants aged 0–6 months in the Bojongkerta area of Bogor City. Hypnobreastfeeding is a psychological approach that combines relaxation techniques, positive affirmations, and education about breastfeeding to help mothers feel more confident in the breastfeeding process. This study used a quasi-experimental approach with a pre- and post-test design without a control group. A total of 31 breastfeeding mothers participated in this training, which included education about breastfeeding, positive affirmation techniques, and relaxation exercises. Data analysis results showed a significant increase in mothers' knowledge and attitudes towards breastfeeding after the training intervention. Furthermore, the study also recorded an increase in the success of exclusive breastfeeding during the observation period. Based on these findings, it can be concluded that hypnobreastfeeding is an effective approach to supporting the empowerment of breastfeeding mothers at the community level. This method offers a psychologically based solution to overcome social barriers that affect the success of exclusive breastfeeding.